Prospective cohort study of Helicobacter pylori infection on the risk of nonalcoholic fatty liver disease - Changxi Chen; Sha Si; Juan Du; Hongliang Li (Canadian Science Publishing, 2024)
To investigate the epidemiological connection between nonalcoholic fatty liver disease (NAFLD) and Helicobacter pylori (H. pylori). 6,478 retired and active workers, aged 22-69 years, were included in the study. Their baseline measures of height, weight, waist measurement, body mass index, blood pressure, fasting blood sugar, plasma lipid, liver function index, glycosylated hemoglobin, abdominal ultrasonography, and findings from the line "13 C urea breath test" H. pylori test were analyzed, and follow-up with consistent baseline methods and criteria was performed annually. Over a 4-year period, the prevalence of NAFLD increased by 16.9%, with 612 (18.7%) of those who tested positive for H. pylori developing NAFLD, whereas 484 (15.1%) of those who did not test positive for H. pylori were later diagnosed with new NAFLD (χ2 = 14.862, P < 0.05). One of the risk factors identified in the univariable Cox regression model for NAFLD was H. pylori (Hazard Ratio = 1.297; 95.0% confidence interval (CI) 1.150,1.485, P < 0.000); however, H. pylori continued to be an independent factor affecting the risk of NAFLD even after accounting for gender, age, and aspects of the metabolic syndrome (Hazard Ratio = 1.240; 95.0% CI 1.077,1.429, P = 0.003). The growth of NAFLD may be correlated with H. pylori infection.